PENERAPAN MODEL PEMBELAJARAN ACTIVE LEARNING DENGAN MENGGUNAKAN MEDIA FLIP CHART UNTUK MENINGKATKAN PEMAHAMAN KONSEP PESERTA DIDIK KELAS XI IPA SMA NEGERI 1 TANJUNG BUNGA PADA MATERI SISTEM ORGAN - Adrianus Motong Liwun; Dwi Candra Setiawan (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2018)
Learning should be centered on the students centered this is in accordance with the demands of Education Unit Level Curriculum (KTSP). Learning in schools today is still conventional, which is teacher centered so that less reflects a meaningful learning for learners. Implementation of active learning model using flip chart media is expected to improve understanding of students' concept of class XI IPA SMA Negeri 1 Tanjung Bunga on organ system material. This research is a Classroom Action Research (PTK) consisting of two cycles. Population in this research is all student of SMA Negeri 1 Tanjung Bunga with sample is student of class XI IPA SMA Negeri 1 Tanjung Bunga. Improved understanding of learners' concepts can be measured using tests. The success of active learning model using flip chart media is seen through comparison between cycle I with cycle II. Based on the result of cycle I with cycle II, the percentage of concept improvement is 1.06%, the result can be obtained through division of the second cycle gain divided by the acquisition of cycle I (80.95%: 76.19%). From these results it can be concluded that by applying the learning model of active learning by using the medi flip chart can improve understanding of theconcept of learners.